2019
DOI: 10.1371/journal.pone.0207512
|View full text |Cite
|
Sign up to set email alerts
|

Remote access protocols for Desktop-as-a-Service solutions

Abstract: The use of remote desktop services on virtualized machines is a general trend to reduce the cost of desktop seats. Instead of assigning a physical machine with its operating system and software to each user, it is considerably easier to manage a light client machine that connects to a server where the instance of the user’s desktop machine actually executes. Citrix and VMware have been major suppliers of these systems in private clouds. Desktop-as-a-Service solutions such as Amazon WorkSpaces offer a similar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…As such, the use of Cloud ERP to achieve innovation has received growing attention in both academia and practice in contemporary societies. Specifically, a group of four different types of cloud computing services, including Software as a Service (SaaS), Platform as a Service (PaaS), Infrastructure as a Service (IaaS) and Desktop as a Service (DaaS), can offer several strategic solutions (Lee et al, 2021;Magaña et al, 2019;Jarraya and Elloumi, 2022). Therefore, enterprises can utilise such cloud service models to efficiently generate a digital workspace.…”
Section: Theoretical Implications and Future Research Avenuesmentioning
confidence: 99%
“…As such, the use of Cloud ERP to achieve innovation has received growing attention in both academia and practice in contemporary societies. Specifically, a group of four different types of cloud computing services, including Software as a Service (SaaS), Platform as a Service (PaaS), Infrastructure as a Service (IaaS) and Desktop as a Service (DaaS), can offer several strategic solutions (Lee et al, 2021;Magaña et al, 2019;Jarraya and Elloumi, 2022). Therefore, enterprises can utilise such cloud service models to efficiently generate a digital workspace.…”
Section: Theoretical Implications and Future Research Avenuesmentioning
confidence: 99%
“…The average transfer rates were approximately 92 Mb/s downstream and 94.6 Mb/s upstream. These rates are limited by the 100Base-T connectivity of the computers, but are still much faster than the minimum speeds required needed for remote desktop usage [20]. The average measured RTT was 7 ms, which is far below the 150 ms recommendation of ITU-T G.114 standard [13].…”
Section: Local Vdimentioning
confidence: 99%
“…Some papers in the literature have addressed the characterisation of the network requirements for the PCoIP protocol used by Amazon WorkSpaces. In [20,39], it was demonstrated that the video user profile tends to be the most demanding service, requiring a transfer rate of 0.834 Mb/s in the upstream direction and 9 Mb/s in the downstream direction. Therefore, the bandwidth available for our setup is not a bottleneck.…”
Section: Public Vdi: Amazon Workpacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fitur utamanya yaitu pembuatan mobile taking order, mengelola mobile taking order, melakukan pengecekan order yang sudah dilakukan, dan melakukan setoran pembayaran terhadap piutang golfer. Koneksi antara POS System dan smartphone di server pusat menggunakan koneksi RDC (Remote Desktop Computing) System [4]. Dengan munculnya system mobile taking order ini penulis berharap club house dapat memaksimalkan POS system dan smartphone untuk meningkatkan produktivitas para waitress dan kasir yang nantinya akan meningkatkan keuntungan bagi club house.…”
Section: Pendahuluanunclassified